Analisis Kepemimpinan Demokratis Kepala Sekolah Dalam Meningkatkan Kedisiplinan Peserta Didik Kelas XII di MA Nurul Iman Tahun Ajaran 2024-2025: Penelitian - Riyanto; Miftahus Surur; Fathor Rakhman (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Education serves to transfer knowledge, shape character, and improve the quality of human resources, with schools as strategic institutions. Educational success is highly dependent on the leadership of the principal, particularly in building a culture of discipline. Democratic leadership is believed to be able to create a participatory atmosphere so that all school elements contribute optimally. This study focuses on MA Nurul Iman under the Nurul Imam Islamic Boarding School, which accepts students from both Islamic boarding school and non-Islamic boarding school backgrounds, resulting in variations in discipline. Initial observations indicated discipline problems, such as incomplete school attributes, truancy, and tardiness. The study aims to analyze the role of the principal's democratic leadership in improving the discipline of grade XII students in the 2024–2025 academic year, with the hope that the principal can serve as a role model and create discipline awareness through the example of educators.